2021
DOI: 10.1080/02673843.2021.1908903
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ and young adults’ experiences of loneliness and their thoughts about its alleviation

Abstract: Society has undergone rapid changes over the last decade affecting adolescents and their mental health as well as experiences of loneliness. The aim of this study is to examine loneliness from adolescents' and young adults' perspectives. Data was collected through semi-structured interviews with eleven (n = 11) Finnish adolescents and young adults aged 17-28 and analysed using qualitative content analysis. Two main themes and six subthemes were found. The main themes were: risk factors for loneliness and diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 40 publications
2
35
0
Order By: Relevance
“…Although more studies are required to further investigate a putative cortical versus subcortical association of loneliness across aging groups, it is important to note that risk factors for loneliness are not comparable across life stages. For instance, a recent study with Finnish adolescents and young adults reveled that this negative feeling is related to social transitions and expectations, group differences, former destructive experiences or negative self-image among others ( Sundqvist and Hemberg, 2021 ); while for middle-aged and older adults the most important factors contributing to loneliness are the loss of a spouse, frequency of contact with significant friends or family and the number of voluntary groups one is engaged to Cacioppo et al (2015) . It is also important to note that while the abovementioned studies focusing on cross-sectional associations between loneliness and brain structure used Voxel-Based Morphometry (VBM), we had a dual and different focus with a longitudinal approach: first, the hypothesis driven approach targeting the hippocampus as a subcortical structure related to emotional processing and episodic memory; and second, the exploratory approach of vertex-wise cortical thickness.…”
Section: Discussionmentioning
confidence: 99%
“…Although more studies are required to further investigate a putative cortical versus subcortical association of loneliness across aging groups, it is important to note that risk factors for loneliness are not comparable across life stages. For instance, a recent study with Finnish adolescents and young adults reveled that this negative feeling is related to social transitions and expectations, group differences, former destructive experiences or negative self-image among others ( Sundqvist and Hemberg, 2021 ); while for middle-aged and older adults the most important factors contributing to loneliness are the loss of a spouse, frequency of contact with significant friends or family and the number of voluntary groups one is engaged to Cacioppo et al (2015) . It is also important to note that while the abovementioned studies focusing on cross-sectional associations between loneliness and brain structure used Voxel-Based Morphometry (VBM), we had a dual and different focus with a longitudinal approach: first, the hypothesis driven approach targeting the hippocampus as a subcortical structure related to emotional processing and episodic memory; and second, the exploratory approach of vertex-wise cortical thickness.…”
Section: Discussionmentioning
confidence: 99%
“…School is a critical arena for adolescents’ development (García-Moya et al, 2019 ), and school belongingness or connectedness has been shown to promote mental health and well-being (Lester et al, 2013 ) as well as psychosocial functioning and academic performance (Allen et al, 2018 ). Previous research shows that important factors to alleviate loneliness among adolescents are interventions focusing on strengthening the self, working on safe environments, and inclusion (Sundqvist & Hemberg, 2021 ). Thus, it is important to support adolescents’ sense of inclusion and belonging to promote their health and well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents are at heightened risk of loneliness due to developmental shifts in social networks, where the primary source of socialisation shifts from parents towards peers (Goossens, 2018;Laursen & Hartl, 2013). Adolescence is also marked by periods of transition (e.g., moving from primary to secondary school, or leaving home), which is a known risk factor for increased loneliness (Siva 2020;Sundqvist & Hemberg, 2021). This may be further compounded by the social stigma surrounding failure to connect with peers (Rokach, 2012) during a period of development in which social connection and peer acceptance is key (Ragelienė, 2016) and loneliness 'taboo' (Mental Health Foundation, 2021).…”
Section: Youth Loneliness and Mental Healthmentioning
confidence: 99%
“…Overall, our findings suggest that loneliness is a crucial lever to improving the mental health of adolescents. Research demonstrates that risk factors for adolescent loneliness include, though are not limited to: experiencing social transitions, for example, moving from primary school to secondary school, or starting university, (Siva, 2020;Sundqvist & Hemberg, 2021); low socioeconomic position (Madsen et al, 2019;Varga et al, 2014); having a disability (Maes et al, 2017;ONS, 2019); or being of minority sexual orientation (Gorczynski & Fasoli, 2021;Marquez et al, 2021). Therefore, it may be particularly critical to develop interventions to tackle loneliness and foster meaningful social connections among these groups.…”
Section: Between-school Variation In Mental Health and Differing Effe...mentioning
confidence: 99%